Effects of topping and non-topping on growth-regulating hormones of flue-cured tobacco (Nicotiana tabacum L.)—a proteomic analysis - Gu, Kaiyuan; Yang, Li-E.; Ren, Ke; Luo, Xianxue; Qin, Xiao; Op de Beeck, Michiel; He, Conglian; Jian, Li; Chen, Yi (Frontiers in Plant Science, 2023)
Until now, the mechanism underlying the impact of topping on hormone regulation in tobacco plants remains unclear, and most studies investigating the hormone signaling pathways in plants rely on genes or transcriptional pathways. This study examines the regulatory mechanisms of hormones in the roots and leaves of tobacco plants with and without topping at the protein level. The results demonstrate that, compared to non-topped plants, topping leads to a decrease in the levels of IAA (Auxin), ABA (Abscisic acid), and GA (Gibberellin) hormones in the leaves, while the content of JA (Jasmonic acid) hormone increases. Furthermore, in the roots, topping results in an increase in the levels of IAA, ABA, and JA hormones, along with a decrease in GA content. In the leaves, a total of 258 significantly different proteins were identified before and after topping, with 128 proteins up-regulated and 130 proteins down-regulated. In the roots, there were 439 proteins with significantly different quantities before and after topping, consisting of 211 up-regulated proteins and 228 down-regulated proteins. Notably, these proteins were closely associated with the metabolic and biosynthetic pathways of secondary metabolites, as indicated by functional categorization. When integrating the hormone changes and the proteomics results, it is evident that topping leads to increased metabolic activity and enhanced hormone synthesis in the root system. This research provides a theoretical foundation for further investigations into the regulation and signaling mechanisms of hormones at the protein level before and after topping in plants.